A bioassay system of autologous human endothelial, smooth muscle cells, and leukocytes for use in drug discovery, phenotyping, and tissue engineering. Issue 1 (5th December 2019) - Ahmetaj‐Shala, Blerina; Kawai, Ryota; Marei, Isra; Nikolakopoulou, Zacharoula; Shih, Chih‐Chin; Konain, Bhatti; Reed, Daniel M.; Mongey, Róisín; Kirkby, Nicholas S.; Mitchell, Jane A.
Abstract: Blood vessels are comprised of endothelial and smooth muscle cells. Obtaining both types of cells from vessels of living donors is not possible without invasive surgery. To address this, we have devised a strategy whereby human endothelial and smooth muscle cells derived from blood progenitors from the same donor could be cultured with autologous leukocytes to generate a same donor "vessel in a dish" bioassay. Autologous sets of blood outgrowth endothelial cells (BOECs), smooth muscle cells (BO‐SMCs), and leukocytes were obtained from four donors. Cells were treated in monoculture and cumulative coculture conditions. The endothelial specific mediator endothelin‐1 along with interleukin (IL)‐6, IL‐8, tumor necrosis factor α, and interferon gamma‐induced protein 10 were measured under control culture conditions and after stimulation with cytokines. Cocultures remained viable throughout. The profile of individual mediators released from cells was consistent with what we know of endothelial and smooth muscle cells cultured from blood vessels. For the first time, we report a proof of concept study where autologous blood outgrowth "vascular" cells and leukocytes were studied alone and in coculture. This novel bioassay has usefulness in vascular biology research, patient phenotyping, drug testing, and tissue engineering.